Knowledge Management: For New Times With New Technologies - Jauhari, Ankur; Pratihar, Aditya Singh (Prabandhan: Indian Journal of Management, 2010)
Knowledge Management (KM) comprises of a range of practices used in an organisation to identify, create, represent, distribute and enable adoption of insights and experiences. Such insights and experiences comprise of knowledge, either embodied in individuals or embedded in organizational processes or practices. An established discipline since 1995, KM includes courses taught in the fields of business administration, information systems, management, and library and information sciences. More recently, other fields, to include those focused on information and media, computer science, public health, and public policy, have also started contributing to KM research. Many large companies and non-profit organisations have resources dedicated to internal KM efforts, often as a part of their ’Business Strategy’, ’Information Technology’, or ’Human Resource Management’ departments. Several consulting companies also exist that provide strategy and advice regarding KM to these organisations.KM efforts typically focus on organisational objectives such as improved performance, competitive advantage, innovation, the sharing of lessons learned, and continuous improvement of the organisation. KM efforts overlap with Organisational Learning, and may be distinguished from it by a greater focus on the management of knowledge as a strategic asset and a focus on encouraging the exchange of knowledge. KM efforts can help individuals and groups to share valuable organizational insights, to reduce redundant work, to avoid reinventing the wheel per se, to reduce training time for new employees, to retain intellectual capital as employees’ turnover in an organisation, and to adapt to changing environments and markets.